2022
DOI: 10.1515/sjpain-2021-0102
|View full text |Cite
|
Sign up to set email alerts
|

High score of dizziness-handicap-inventory (DHI) in patients with chronic musculoskeletal pain makes a chronic vestibular disorder probable

Abstract: Objectives In patients with a vestibular disorder a high score of dizziness-handicap-inventory (DHI) is common. Patients with chronic lithiasis of multiple canals benign paroxysmal positional vertigo (mc-BPPV) can have incapacitating symptoms, e.g. headache, neck pain, musculoskeletal pain, and cognitive dysfunction. Patients with chronic musculoskeletal pain with few objective findings at an ordinary examination of the musculoskeletal system together with unsuccessful interventions can eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The DHI proves valuable, consistent, and valid in gauging self-assessed impairment linked to dizziness. It has been validated in cases of acute [ 25 ] and recurrent [ 26 ] vestibular disorders, as well as chronic dizziness [ 27 ]. Elevated DHI scores have been documented in VM patients [ 28 ], and the questionnaire has been employed to examine the effects of personalized vestibular rehabilitation (VR) programs on balance, gait performance, and self-perceived handicap in VM patient groups [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DHI proves valuable, consistent, and valid in gauging self-assessed impairment linked to dizziness. It has been validated in cases of acute [ 25 ] and recurrent [ 26 ] vestibular disorders, as well as chronic dizziness [ 27 ]. Elevated DHI scores have been documented in VM patients [ 28 ], and the questionnaire has been employed to examine the effects of personalized vestibular rehabilitation (VR) programs on balance, gait performance, and self-perceived handicap in VM patient groups [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scientists have long been interested in the relationship between dizziness/balance and pain 39 . The vicious cycle of pain and balance interact through central re exes, and muscle tone control [39][40][41][42] . Malmstrom et al 8 showed in a study of patients referred to a vestibular disorders clinic for balance disorders and a psychiatric clinic for anxiety or depression that there may be an interaction between persistent dizziness, mood, and Neck-Shoulder-Back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Malmstrom et al 8 showed in a study of patients referred to a vestibular disorders clinic for balance disorders and a psychiatric clinic for anxiety or depression that there may be an interaction between persistent dizziness, mood, and Neck-Shoulder-Back pain. Iglebekk et al 42 Used the Structured symptom questionnaire, Modi ed dizziness handicap inventory (DHI), and DHI subscales to investigate a group of patients with chronic musculoskeletal pain in Norway and Denmark. The investigations concluded that patients with complex chronic musculoskeletal disorders might have undiagnosed vestibular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…O impacto da tontura na qualidade de vida, medido pelo DHI, sempre esteve associado à dor no grupo não tratado. Novamente os achados concordam com dados da literatura que mostram alta frequência de alteração no DHI em pacientes com dor crônica musculoesquelética e apresentam alteração vestibular crônica (Iglebekk;Tjell, 2022). A associação entre DHI e tontura foi forte 6.…”
Section: Escala Visual Analógicaunclassified